Degradation of Poly (3-Hydroxybutyrate) (PHB) by Bacillus gelatini isolated from Vietnam - Van Anh, Trinh Thi; Kim Toan, Ngo Thi; Huy, Nguyen Quang (Academia Journal of Biology, 2012)
Poly (3-hydroxybutyrate) (PHB) is a natural polymer produced by many bacteria as a means to store carbon and energy. PHB have attracted commercial biotechnological interest because of their biodegradability and biocompatibility. Several aerobic and anaerobic PHB-degrading microorganisms have been isolated from soil, activated and aerobic sludge, seawater and lake water. The percentage of PHB-degrading microorganisms in the environment was estimated to be 0.5 - 9.6% of the total colonies. Majority of the PHB-degrading microorganisms were isolated at ambient or mesophilic temperatures and a few of them were able to degrade PHB at higher temperature. The composting at high temperature is one of the most promising technologies for recycling biodegradable plastics and the thermophilic microorganisms that could degrade polymers play an important role in the composting process. Thus, microorganisms that are capable of degrading various kinds of polyesters at high temperatures are of interest. In this study, we have isolated 11 thermophilic PHB-degrading bacteria strains. Among them strain B2 was able to use PHB as a carbon source for growth at high temperature (50oC). This bacteria grew at temperatures between 37 - 60oC, at NaCl concentration between 0.5 - 3% and at pH between 5 - 8. This strain was able to used sucrose, D-glucose, fructose, mannose... but not used D (+) glucosamin. This strain produced some extracellular enzymes such as cellulase, protease, catalase but not amylase.16S rDNA sequence analysis of strain B2 indicated that this novel isolation was related phylogenetically of Bacillus genus. Base on phenotypic, chemotaxonomic and phylogenetic results for strain B2, we describe a novel species named Bacillus gelatini. After 30 days of cultivation in the media with the concentration of PHB in the range of 1-2 g/l, B. gelatini degraded more than 50% total amount of PHB added. Strain B. gelatini can degrade not only PHB but also PLA, PCL at the rate of more than 20% after 20 days cultivation. For further studies, the purification of an extracellular PHB depolymerase from B. gelatini is necessary.